Multiculturalism in Javanese Humor (A Case in 'Sing Lucu' Rubric of Panjebar Semangat Magazine) - Valentina Widya Suryaningtyas; Nina Setyaningsih (Fakultas Bahasa dan Budaya Asing (FBBA), Universitas Muhammadiyah Semarang, 2018)
Crystal (1998) points out everyone plays with language or responds to language. We play with language when we manipulate it as a source of enjoyment, either for ourselves or for the benefit of others. We take some words, phrases, sentences, and other linguistic features and make them do things that they do not normally do. This language manipulation can result in humor. Humor has formed a substantial part of Javanese culture. Some jokes in Javanese contain local wisdom and this, according to Bascom (in Wijana, 2003) plays an important role to maintain the social and cultural norms. This paper examines the humor used in Sing Lucu rubric which contains jokes in Panjebar Semangat magazine. In Indonesia, there are only a few printed media that specialize in Javanese language and culture. One of them is Panjebar Semangat. It is a magazine that maintains Javanese culture, especially by the use of Javanese language and Javanese related contents. This paper aims to identify the types of humor and to explore the multiculturalism through the Javanese language expression. This study is framed by drawing on theories on humor, language play, and ambiguity. The result shows that there are three types of humor used in Sing Lucu: positive, negative, and neutral. Positive and neutral jokes have entertaining contents, while negatives jokes contain stereotyping of certain races. Some jokes are not based on facts and therefore they do not always represent certain races stereotyped in such jokes.